Enhancing actions of peptides derived from the γ-chain of fetal human hemoglobin on the immunostimulant activities of monophosphoryl lipid A. Issue 3 (April 2016) - Ulmer, Artur J; Kaconis, Yani; Heinbockel, Lena; Correa, Wilmar; Alexander, Christian; Rietschel, Ernst Th; Mach, Jean-Pierre; Gorczynski, Reginald M; Heini, Adrian; Rössle, Manfred; Richter, Walter; Gutsmann, Thomas; et al.
Hemoglobin and its structures have been described since the 1990s to enhance a variety of biological activities of endotoxins (LPS) in a dose-dependent manner. To investigate the interaction processes in more detail, the system was extended by studying the interactions of newly designed peptides from the γ-chain of human hemoglobin with the adjuvant monophosphoryl lipid A (MPLA), a partial structure of lipid A lacking its 1-phosphate. It was found that some selected Hbg peptides, in particular two synthetic substructures designated Hbg32 and Hbg35, considerably increased the bioactivity of MPLA, which alone was only a weak activator of immune cells. These findings hold true for human mononuclar cells, monocytes and T lymphocytes. To understand the mechanisms of action in more detail, biophysical techniques were applied. These showed a peptide-induced change of the MPLA aggregate structure from multilamellar into a non-lamellar, probably inverted, cubic structure. Concomitantly, the peptides incorporated into the tightly packed MPLA aggregates into smaller units down to monomers. The fragmentation of the aggregates was an endothermic process, differing from a complex formation but rather typical for a catalytic reaction.